Measuring the contribution of manufacturing industries to the gross domestic product in algeria, during the period 1990-2023 using the ARDL model - Yahiaoui, Mohamed; Djorfi, Zakaria (The International tax journal, 2025)
The industrial sector is regarded as a crucial economic domain for all nations, both developed and developing, as it significantly contributes to economic growth by facilitating economic interconnections and interlinking various industrial sectors. Furthermore, it establishes diverse industrial frameworks that enhance the industrial sector, thereby maximizing the export potential of the national economy and fostering economic stability. This study seeks to ascertain the short- and long-term relationship between manufacturing output and internal GDP from 1990 to 2018, employing the autoregressive distributed lag (ARDL) model. The findings indicate a balanced relationship in both the short and long term, alongside the absence of autocorrelation issues in the error sequence, with stability maintained over time. The study concludes a statistically significant direct relationship between GDP and the manufacturing sector.